Fundamentals of evidence based medicine - Prasad, Kameshwar (Springer India, 2014)
This is a basic book on evidence-based medicine (EBM). It starts with an introduction to the topic. It outlines the relationship between EBM and research and quality of care. Then It goes on to cover the most commonly used modules of EBM, i.e. therapy, diagnosis, prognosis and meta-analysis. Each module starts with an introduction to fundamental concepts, and description of the related research process, and then follows the critical appraisal of related type of research artcle. At the end, it covers the different systems of grading of level of evidence and strength of recommendations. The book also has three examples of critical appraisal on diagnosis, therapy, and meta-analysis.